Consumer behavior analysis based on resonant ads and non-resonant ads for high and low involving product categories - Punnanchira, Chackochan; G. Kulkarni, S (International Journal of Engineering and Technology, 2018)
This study aims to deal with the aspect of consumer behavior in relation with the resonance of advertisement of low and high involvement products. An online survey using questionnaire was conducted on 74 consumers to perform qualitative analyses so as to witness the influence of resonance in advertising on various consumer behavior factors. The results of the survey revealed that resonance in advertisements is not an important or only element to control the purchasing intention of consumers. There lies other factor like age, gender, brand loyalty etc. which influences the consumer preferences. Even though the resonance in advertisement did not affect the consumer behavior significantly, it still helped in notifying the consumers with latest updates of their preferred brand/products. The findings of this study can be used by different companies to understand the consumer behavior and invest in more yielding strategies. Although a number of studies exist on understanding the impact of advertisement effectiveness on consumer behavior, there are none pertaining to the resonance in advertising. Hence the discoveries of this study are extremely useful in understanding the relation between the resonance in advertisements and consumer behavior.Â Â